Unmasking Gender Discrimination At The European Court Of Human Rights: Why Sexual Violence Jurisprudence Must Evolve (International Journal of Environmental Sciences, 2025)
This article examines how the European Court of Human Rights (ECtHR) addresses violence against women as a form of sex- and gender-based discrimination under Article 14 of the European Convention on Human Rights. Drawing on the evolving standards of the CEDAW Committee and the Council of Europe’s Istanbul Convention, the paper situates violence against women - including domestic violence and sexual violence - within a structural discrimination framework. It highlights the Court’s significant progress in recognising domestic violence as a form of discrimination, as demonstrated in landmark cases such as Opuz v. Turkey, Eremia, Tkhelidze, and A and B v. Georgia. However, the analysis reveals a persistent gap in the Court’s treatment of rape and sexual violence, where it has yet to apply the same standards of investigating sexist and misogynistic motives that it requires in cases involving racist or homophobic hate crimes. Drawing on feminist legal scholarship, the paper argues that unmasking sexist motives in rape cases is essential to dismantling the patriarchal norms that hinder justice for sexual violence. The article calls for the ECtHR to align its anti-discrimination jurisprudence and require states to investigate and address the discriminatory motives of the perpetrators of rape and sexual violence cases, like it has done in relation to cases involving racist and homophobic violence. By doing so, the ECtHR can better fulfil its role in securing women’s substantive equality and freedom from violence in practice.